BAGAIMANA KEPUASAN KERJA KARYAWAN HOTEL BERBINTANG DIJAKARTA – INDONESIA DAPAT DIPENGARUHI OLEH KEPEMIMPINAN, KOMUNIKASI DAN MOTIVASI (Jurnal Ilmiah Pariwisata, 2015)
Various studies have been conducted to see how the job satisfaction of employees can be affected by many variables such as motivation and leadership. The problem that occurs is that the level of employee satisfaction greatly affect its performance in service to consumers. For those reasons, job satisfaction was found to be significant and should be antecendent constituent variables such as leadership, motivation and communication. This study aims to model the effect of leadership, motivation and communication on the level of employee satisfaction. This research was conducted in two (2) phases. First performed in two 4 and 5 star hotels in Jakarta, the second phase will be carried out in two-star hotels 3 and 2. This distinction aims to get results if the employee satisfaction in terms of leadership, motivation and communication will be the same or different in the hotel with star category different. The method used descriptive correlational, to test four hypotheses model builders. Sample withdrawal method by accident (accidental sampling) is used to obtain data from seperangat questions to test constructs built. Analysis used structural equation modeling with the help of software Lisrell. The relationship of service quality and job satisfaction resulted in a strong relationship of 0.622 , it indicates that employees are satisfied to work so as to provide a quality service for hotel guests .
Keywords: Leadership, Motivation, Communication, service quality and Job Satisfaction